2022
DOI: 10.1088/1361-648x/ac4f7d
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network potential for Au20 clusters based on the first-principles

Abstract: The search of ground-state structures (GSS) of gold (Au) clusters is a formidable challenge due to the complexity of potential energy surface (PES). In this work, we have built a high-dimensional artificial neural network (ANN) potential to describe the PES of Au20 clusters. The ANN potential is trained through learning the GSS search process of Au20 by the combination of density functional theory (DFT) method and genetic algorithm (GA). The root mean square errors (RMSE) of energy and force are 7.72 meV/atom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…These results were all obtained with a potential derived using data from all structures simultaneously, i.e the one whose statistics are shown in Figure 4 . Cao et al [ 23 ] studied structures of several small gold clusters including Au , and found a local minimum which resembles the one shown here. Ford et al [ 15 ] also found a similar structure at approximately the same energy above the global minimum.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…These results were all obtained with a potential derived using data from all structures simultaneously, i.e the one whose statistics are shown in Figure 4 . Cao et al [ 23 ] studied structures of several small gold clusters including Au , and found a local minimum which resembles the one shown here. Ford et al [ 15 ] also found a similar structure at approximately the same energy above the global minimum.…”
Section: Resultssupporting
confidence: 79%
“…The other two structures have a cage-like form and a more open flatter form, respectively. Note that related studies have mostly looked at larger clusters [ 20 , 21 , 22 , 23 ], primarily at structures only, but as we wanted to benchmark against an ab-initio MD run we chose this cluster as being computationally manageable but still able to cover the properties of interest.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported that Au n (n = 16-25) prefer the pyramid-based bulk fragment structures related to Au 20 [14]. However, many researchers have proposed different candidate structures, for example, hollow cage Au 16 given out by Cao et al [15], flat cage Au 16 by Bulusu and Zeng [16], hollow cage Au 17 and Au 18 [16], flat cage Au 24 [17] and Au 25 [18]. Obviously, there is controversy about the stable structures in the range of medium-sized Au clusters, and considerable work remains to be done.…”
Section: Introductionmentioning
confidence: 99%
“…In order to find the stable structures of Au clusters, enormous work has been carried out experimentally and theoretically so far [13][14][15][16][17][18]. Li et al proposed a tetrahedral structure of Au 20 which has been proved to be the most stable structure of Au 20 in experiment [13].…”
Section: Introductionmentioning
confidence: 99%